Development of Learning Media Based on Video Tutorials on the Subjects of Software Applications and Building Interior Design at SMK Negeri 1 Sumatera Barat - Juniarti, Silvia Andra; Yustisia, Henny (CIVED, 2024)
This research was motivated by the problem encountered, namely the lack of use of media in the learning process of Software Applications and Building Interior Design. This research uses the type of research and development (R&D). This development model refers to the development model (DDD-E) with 4 stages, namely Decide, Design, Development, Evaluate. The subjects of this research were media experts, material experts and class XII Competency Design Skills Modeling and Building Information, SMK Negeri 1 Sumatera Barat, 30 students. This research instrument is in the form of a validation sheet to obtain product validation data, and a student respondent questionnaire to obtain product practicality test results. The research results show that the validity of the material is in the very valid category with an achievement level of 88.4%. Media validity with an achievement level of 90.65% in the very valid category and practicality test with an achievement level of 89.53% in the very practical category. The conclusion of this research is that the learning media developed is valid and practical for use in the learning process Software Application and Building Interior Design class XII Competency Design Skills Modeling and Building Information, SMK Negeri 1 Sumatera Barat.